MONITORING THE RESPONSE TO TYROSINE KINASE INHIBITOR (TKI) TREATMENT IN CHRONIC MYELOID LEUKEMIA (CML) - Ibrahim C. Haznedaroglu (Mediterranean Journal of Hematology and Infectious Diseases)
The aim of oral tyrosine kinase inhibitor (TKI) treatment in chronic myeloid leukemia (CML) is to get ideal hematological, cytogenetic, molecular responses at the critical time-points. The depth of the response obtained with TKI and time to achieve this response are important for the prediction of prognosis in the patient with CML. The high efficacy of the TKI treatment of CML has prompted the need for accurate methods to monitor response at levels below the landmark of CCyR. Quantification of BCR-ABL transcripts has proven to be the most sensitive method available and has shown prognostic impact with regard to progression-free survival. European LeukemiaNet (ELN) molecular program harmonized the reporting of results according to the IS (Internatıonal harmonization of Scale) in Europe. The aim of this review is to outline monitoring the response to optimal TKI treatment based on the ELN CML 2013 recommendations from the clinical point of view as a physician. Careful cytogenetic and molecular monitoring could help selecting the most convenient TKI drug and to optimize TKI treatment. Excessive monitoring may have an economical cost but failure to optimize TKI treatment may result in CML disease acceleration and death.